Use of mind mapping method to improve social studies learning outcomes of elementary school students - Deni Okta Nadia; Yeni Erita; Nofia Henita; Rahmi Yulia (LPPMPK-Sekolah Tinggi Teknologi Muhammadiyah Cileungsi, 2023)
The low student learning results in social studies are the background for this study, and the learning that takes place typically is monotonous so that students find it difficult to retain the subject that has been covered. The aim of this study or service is to report how the mind mapping technique improved student learning results in class VI at SDN 14 Simpang Ampek. This study is a two-cycle classroom action research (CAR) that combines qualitative and quantitative methods. Whereas cycle two just has one meeting and cycle one has two meetings. The findings revealed that cycle I meeting 1 student learning objectives had an average score of 74.01 and a completion rate of 47.4%. Meeting 2 came in second with an average of 82.41 and a completion rate of 78.9%. Then, it improved once more in cycle II meeting 1, reaching an average of 89.6 and a 100% completion rate. Thus, it can be inferred that by adopting the mind mapping method in elementary schools, kids' social studies learning results can be enhanced